PENGARUH EFEKTIVITAS PENGGUNAAN DAN KEPERCAYAAN TERHADAP TEKNOLOGI SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA INDIVIDUAL PADA PASAR SWALAYAN DI KOTA DENPASAR - RATNA SARI, MARIA M. (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009), 2009)
This reseach intends to investigate yhe effect of usage effectiveness and trust to accounting information systems (AIS) technology on individual performance. Analysis is conducted aims multiple linier regression. The results show that usage effectiveness affects individual performance positively and significantly, that is 51,7%. Futhermore, trust to AIS technology also has positive an significant impact to individual performance of 17,7%. This is strengthened by respondent answers who have trust level on information system technology as high as 84%. Simultaneusly, usage effect and trust affect individual performance positively and significant with contribution 56,8%.
Keywords: usage effectiveness, trust, accounting information systems (AIS) technology, individual performance.